Flipped Classroom and Digital Technology in EFL Reading: A Deep Learning Approach - Siti Samsiatun Ni'mah; Agus Wardhono (Darul Ilmi Bina Insan Foundation, 2026)
This study investigated the implementation of a flipped classroom integrated with digital technology and a deep learning approach to improve EFL students’ reading comprehension at Universitas PGRI Ronggolawe Tuban. The study employed a pre-experimental quantitative design using a one-group pretest-posttest model. Eighteen fourth-semester students from the English Language Education Study Program, Faculty of Teacher Training and Education, participated in the study during the odd semester of the 2026/2027 academic year. The participants were selected through total sampling because only one class was involved. The instruments consisted of a reading comprehension test, pre-test, post-test, treatment materials, instructional videos, digital reading texts, YouTube-based learning activities, documentation of students’ scores, and a questionnaire. The data were analyzed using SPSS through descriptive statistics, the Shapiro-Wilk normality test, and hypothesis testing. Since the comparison of pre-test and post-test scores was analyzed using the Wilcoxon Signed Ranks Test, the results showed that 6 students achieved higher post-test scores, 1 student obtained a lower post-test score, and 11 students had equal scores. The Wilcoxon test yielded Z = -1.951 with Asymp. Sig. (2-tailed) = .051. These findings indicate that students’ reading comprehension showed positive directional improvement after the treatment, although the statistical result was slightly above the conventional significance level of .05. The questionnaire instrument demonstrated very high reliability, with Cronbach’s Alpha = .988 for 29 items. The study suggests that flipped classroom learning supported by digital technology can create opportunities for more active and independent EFL reading learning, but stronger experimental designs and larger samples are recommended for future research.